KUALITAS PRODUK SEBAGAI VARIABEL INTERVENING ANTARA PENGARUH LIFE STYLE TERHADAP MINAT BELI MOBIL AGYA DI PASAMAN BARAT - Citra Suci Mantauv (Jurnal Apresiasi Ekonomi, 2016)
This study aimed to see how the variables Lifestyle affect intantion and see also whether the Quality of Product role as an intervening variable. From the results of this study, the variables Life Style (X) significantly affects Intantion (Y), where the regression coefficient is 0.452 with a significant level of 0.000. However, the value of regression coefficient Life Style (X) has decreased from 0.452 into 0.263. Variable Quality of Product (I) as an intervening variable significant effect on Intantion (Y) with regression coefficient is 0.347 and significant level of 0.000. The amount of influence Life Style (X) to Intantion (Y) is 0.532 (R2 = 5.32). In other words, an increase in the effect of variable Life Style (X) to Intantion (Y) amounted to 16.2%, or from 53.2% to 6.97%. It can be interpreted that the variable Quality of Product (I) partially mediate the relationship between the variables Life Style (X) to Intantion (Y). Keywords : Life Style, Quality of Product, Intantion